Areas for use of PEEK material in dentistry - Tekin, Samet; Cangul, Suzan; Adıgüzel, Özkan; Değer, Yalçın (My University, 2018)
Polyetheretherketone (PEEK) material is a polycyclic, aromatic,thermoplastic polymer that is semi-crystalline and has a linearstructure. PEEK has good mechanical and electrical properties such asresistance to high temperature and resistance to hydrolysis. Inaddition, because of the property of high biocompatibility, use of PEEKhas increased in orthopedic and trauma cases. The most characteristicproperty of PEEK material is that it has a low elasticity modulus, closeto that of bone. It has been suggested that stress-based problemscould be reduced with this material due to the low elasticity modulus.In the light of this information, PEEK material could be considered asan alternative to conventional materials in the field of dentistry.
Keywords: Malzeme Bilimleri; Tekstil; Diş Hekimliği; Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Kâğıt ve Ahşap; Malzeme Bilimleri; Kaplamalar ve Filmler; Malzeme Bilimleri; Biyomalzemeler; Malzeme Bilimleri; Seramik; Malzeme Bilimleri; Kompozitler